Aryl Isoprenoids in Crude Oils of the Nyurol'ka Depression (Southeast of Western Siberia); Petroleum Chemistry; Vol. 57, iss. 1 - Chirkova D. Yu.; Krasnoyarova N. A. Nataljya; Serebrennikova O. V. Olga Viktorovna; Olenev Y. V. Yaroslav Valerjevich (2017, 2017)
Title screen